Digital Literacy Among Communication Studies Students in Denpasar in the Age of Deepfakes - Felicianus Jaya Pranata; I Nyoman Indra Kumara (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid advancement of digital technology and artificial intelligence has reshaped the landscape of mass communication, transforming audiences from passive recipients into active content producers. This shift has heightened both the opportunities and the risks associated with digital media use, particularly with the emergence of deepfake technology—AI-generated audio or video designed to mimic real individuals. Deepfakes have introduced new challenges related to misinformation, reputational harm, privacy violations, and declining public trust. In this context, digital literacy becomes essential, especially for Communication Science students who occupy a strategic position as both active media users and future information gatekeepers. This study investigates the digital literacy of Communication Science students in Denpasar in responding to deepfake phenomena. Using a descriptive qualitative method, data were collected through observations, semi-structured interviews, and documentation to explore students’ skills, critical understanding, ethical awareness, and participation in digital environments. The findings reveal that students possess strong digital literacy in terms of technical ability, critical evaluation of information, and ethical considerations when engaging with digital content. However, their involvement in digital literacy advocacy remains limited, indicating the need for more structured educational initiatives. Overall, the study highlights the importance of integrating deepfake awareness and ethical digital literacy into communication education to strengthen students’ resilience against AI-driven media manipulation and to promote a more responsible and informed digital society.